PENGARUH METODE PROBLEM POSING TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATA PELAJARAN EKONOMI MATERI PAJAK - Citra Anggreini; Ikaputera Waspada; Eeng Ahman (Sosio-Didaktika: Social Science Education Journal, 2020)
This article aims differ to solve student problems in tax material economic subjects using the problem posing method. This research was conducted at SMAN 1 Ciwidey, Bandung Regency. The subjects of this study were students of class XI majoring in Social Science. The method to be used is quasi-experimental to find out the treatment effect. The results of the data show the influence of the ability to solve issues by using problem solving methods on tax material. Based on these results, it is recommended that using the method of problem posing to improve students' problem solving abilities.Keywords: problem posing, problem solving ability, economic subjects.